Study of Transition Metal Complexes of Some Oximic Ligands - G. Kelkar, Jitendra; Mehta, B.H. (Asian Journal of Chemistry, 2012)
Oximic ligands were synthesized using 2-hydroxy-1-napthaldehyde and 2,4-dihydroxyacetophenone. Cobalt(II), Nickel(II), copper(II) complexes of oximes were synthesized having metal to ligand stoichiometry 1 : 2. The ligands and complexes were diagnosed for their analytical parameters and various spectral features. The structures of the complexes were proposed on the basis of electronic absorption spectra and magnetic susceptibility data.